Proportion of food insecurity and its sociodemographic correlates among Spanish adolescents: the EHDLA study - Cisneros-Vásquez, Emily; López-Moreno, Miguel; Gutiérrez-Espinoza, Héctor; Olivares-Arancibia, Jorge; Yañéz-Sepúlveda, Rodrigo; Martín-Calvo, Nerea; Smith, Lee; López-Gil, José Francisco (Frontiers in Nutrition, 2025)
IntroductionInsufficient and unequal access to food (i.e. food insecurity [FI]) has a negative impact on health, especially in vulnerable groups such as adolescents. This study determined the prevalence of FI and its sociodemographic correlates among adolescents in the Valle de Ricote, Region of Murcia, Spain.MethodsA secondary analysis was conducted using data from the Eating Healthy and Daily Life Activities (EHDLA) study, which provides a sample of 882 adolescents (median = 14, interquartile range [IQR] = 2) collected during the 2021–2022 academic year. FI was measured using the Child Food Security Survey Module in Spanish (CFSSM-S).ResultsFindings showed a prevalence of FI of 16.2%, with significant sociodemographic disparities. Adolescents from immigrant (n: 67; %: 46.9; odds ratio [OR] = 2.41; 95% CI: 1.38 to 4.21) and diverse (n: 25; %: 17.5; OR=2.04; 95% CI: 1.10 to 3.79) families showed a higher susceptibility to FI. In addition, higher parental education was related to lower FI (university education: n: 13; %: 9.6; OR=0.36; 95% CI: 0.17 to 0.74).ConclusionThese findings highlight the need for targeted public health policies that improve access to nutritious food, enhance parental education, and address socioeconomic inequalities to effectively reduce FI among Spanish adolescents.